2020
DOI: 10.1088/1742-6596/1506/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Biexciton in 2D parabolic quantum dot in magnetic fields

Abstract: We theoretically study biexciton, exciton and charged excitons confined in 2D parabolic quantum dots in a magnetic field by using an unrestricted Hatree-Fork method. The energy and binding energy of exciton and biexciton are presented as a function of magnetic field which show their increase with increasing magnetic field, although small. Our results for the case of strong confinement in InAs/GaAs self-assembled quantum dots show that, while the binding energies of both exciton and negatively charged exciton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The picture of a conventional biexciton-the coupling of two excitons-is replaced by a totally different picture of pair interactions among the four carriers. In our previous works [8][9][10] we showed that the nontrivial Coulomb effect in a small 2D InAs quantum dot supports a bound quadron rather than a traditional biexciton. However, the limitation of these studies is that only the ground states were investigated, and only in a small range of electron-to-hole confinement ratios.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The picture of a conventional biexciton-the coupling of two excitons-is replaced by a totally different picture of pair interactions among the four carriers. In our previous works [8][9][10] we showed that the nontrivial Coulomb effect in a small 2D InAs quantum dot supports a bound quadron rather than a traditional biexciton. However, the limitation of these studies is that only the ground states were investigated, and only in a small range of electron-to-hole confinement ratios.…”
Section: Introductionmentioning
confidence: 87%
“…We focus on self-assembled quantum dots where charged particles can be modeled as a 2D electron-hole system with parabolic potential. As in [8][9][10] we use the model of a system of interacting electrons and holes confined in a 2D quantum dot with a parabolic lateral potential in the presence of a perpendicular magnetic field ⃗ B∥z. Within the effective-mass approximation, for a system of N electrons and M holes (N = M = 2 for biexciton and quadron) the total Hamiltonian is written as…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations